Leadership Accountability and Teacher Motivation in Islamic Junior High Schools: A Mixed Methods Study in Merangin Regency - Hindun Hindun; Norainun Norainun; Siti Marpuah; Khairi Muslimah (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to examine the leadership accountability within Madrasah Tsanawiyah Negeri (MTsN) under the Ministry of Religious Affairs in Merangin Regency and to analyze its relationship with teacher motivation. Methodology: Employing a mixed methods approach with a sequential explanatory design, the study integrates quantitative and qualitative data to obtain a comprehensive understanding of accountability practices and their motivational implications. The quantitative phase involved a survey of 125 MTsN teachers using validated Likert-scale questionnaires measuring leadership accountability and teacher motivation, analyzed through descriptive statistics and Pearson correlation analysis, for qualitative using Miles and Huberman. Main Findings: The results reveal that leadership accountability is predominantly perceived as good, with 94.4% of respondents categorizing it as good or very good, while teacher motivation is similarly high, with 96.0% of teachers falling into these categories. Correlation analysis demonstrates a strong and statistically significant positive relationship between leadership accountability and teacher motivation (r = 0.627, p < 0.01), indicating that higher levels of perceived accountability are associated with increased teacher motivation. Qualitative findings further show that accountability practices are strongest in administrative, reporting, and regulatory dimensions, yet less optimal in affective and humanistic aspects such as recognition, professional support, and responsiveness to teachers’ needs. Novelty/Originality of this study: The novelty of this study lies in its integration of accountability theory with motivational perspectives within the specific context of Islamic secondary education, highlighting that accountability should extend beyond procedural compliance toward ethical, relational, and supportive leadership practices.